Development of qc â Vs Correlation for Depok Silt-Clay - Prakoso, Widjojo A. (Institut Teknologi Bandung, 2010)
Abstract. To initiate the development of cone penetration resistance qc and shear wave velocity Vs correlations of soils from Indonesia, the results of mechanical cone penetration soundings and seismic downhole tests from Depok, West Java area are compiled and analyzed. The soils areÂ predominantly silt-clay soils. The results of the tests are used to develop a qc â Vs correlation. The results and the associated correlation are then compared to qc â Vs correlations from other countries. Abstrak. Dalam rangka pengembangan korelasi antara tahanan konus qc dan kecepatan rambat gelombang geser Vs untuk tanah Indonesia, hasil dari uji sondir mekanik dan uji seismic downhole dari daerah Depok, Jawa Barat dikumpulkan dan dianalisis. Tanah dari lokasi pengujian adalah tanah lanau-lempung. Hasil dari kedua jenis pengujian digunakan untuk mengembangkan korelasi antara qc dan Vs. Korelasi tersebut kemudian dibandingkan dengan korelasi sejenis dari beberapa negara.